Social Stigma and Family Identity Construction in Pulang Balee Marriage among Acehnese Society: A Legal Anthropology Perspective - Mansari Mansari; Zahrul Fatahillah (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Pulang balee marriage is a customary marital practice that continues to exist in Acehnese society, referring to the marriage between an individual and their former sibling-in-law following the death or divorce of a spouse. This practice is commonly regarded as a means of preserving kinship ties, ensuring the continuity of child care, and maintaining family stability, although it may also generate social stigma in certain communities. This study aims to examine pulang balee marriage in relation to the construction of family identity and the strategies employed by families to address social stigma. The research adopts an empirical legal method with a legal anthropology approach. Data were analyzed descriptively and analytically based on the social practices observed within Acehnese communities. The findings indicate that pulang balee marriage functions to strengthen kinship relations, sustain child care, and preserve family continuity after the death of a spouse. Social stigma does not arise uniformly but is shaped by differing community perceptions of customary norms and moral values. Family identity is constructed through an ongoing negotiation between customary values, social perceptions, and lived experiences. To gain social acceptance, families reinforce customary values, emphasize child welfare, and actively participate in community life. This study contributes to legal anthropology by demonstrating that family identity in pulang balee marriage is dynamically negotiated through the interaction of living law, cultural values, and social perceptions. [Perkawinan pulang balee merupakan praktik adat yang masih dijumpai dalam masyarakat Aceh, yaitu perkawinan antara seseorang dengan iparnya setelah pasangan sebelumnya meninggal dunia atau terjadi perceraian. Praktik ini dipandang sebagai upaya menjaga hubungan kekerabatan, keberlangsungan pengasuhan anak, dan stabilitas keluarga, meskipun masih dapat menimbulkan penilaian negatif di sebagian masyarakat. Penelitian ini bertujuan menganalisis praktik perkawinan pulang balee dalam kaitannya dengan pembentukan identitas keluarga dan strategi menghadapi stigma sosial. Penelitian menggunakan metode hukum empiris dengan pendekatan antropologi hukum. Data dianalisis secara deskriptif-analitis berdasarkan praktik sosial yang berkembang dalam masyarakat Aceh. Hasil penelitian menunjukkan bahwa perkawinan pulang balee berfungsi memperkuat ikatan keluarga, menjaga kesinambungan pengasuhan anak, dan mempertahankan hubungan kekerabatan setelah kematian pasangan. Stigma sosial tidak selalu muncul, tetapi dipengaruhi oleh perbedaan pandangan masyarakat terhadap norma adat dan nilai moral. Identitas keluarga terbentuk melalui proses negosiasi antara nilai adat, persepsi masyarakat, dan pengalaman keluarga. Untuk memperoleh penerimaan sosial, keluarga menegaskan nilai-nilai adat, membangun narasi perlindungan anak, serta meningkatkan partisipasi dalam kehidupan bermasyarakat. Penelitian ini menegaskan bahwa identitas keluarga dalam praktik pulang balee dibentuk secara dinamis melalui interaksi antara living law, nilai budaya, dan persepsi sosial masyarakat.]